2017
DOI: 10.1186/s12934-017-0809-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soybean meal fermented by L. plantarum, B. subtilis and S. cerevisieae on growth, immune function and intestinal morphology in weaned piglets

Abstract: BackgroundThe present study compared the effects of soybean meal fermented by three different probiotics organisms with non-fermented soybean meal on growth performance, serum parameters, immune chemistry and intestinal morphology in weaned piglets.MethodsOne hundred and forty-four 35-day old crossbred (Duroc × Landrace × Yorkshire) piglets were randomly allocated into four different dietary treatments (n = 36 per group) containing 0, 5, 10 and 15% fermented soybean meal.ResultsThe piglets fed fermented soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 50 publications
13
56
0
Order By: Relevance
“…Similar findings were reported when fermented rapeseed was fed to broilers where intestinal villus height and villus-to-crypt ratio showed significant improvements [13,37,38]. Feeding of fermented soybean to weaned piglets [39] and Japanese quail [40] also demonstrated significant improvement in villus height but reduced crypt depth along the intestine. However, some studies showed that feeding of lactobacilli fermented liquid feed (feed to water ratio of 1:3) significantly reduced JVH in weaned piglets [41].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar findings were reported when fermented rapeseed was fed to broilers where intestinal villus height and villus-to-crypt ratio showed significant improvements [13,37,38]. Feeding of fermented soybean to weaned piglets [39] and Japanese quail [40] also demonstrated significant improvement in villus height but reduced crypt depth along the intestine. However, some studies showed that feeding of lactobacilli fermented liquid feed (feed to water ratio of 1:3) significantly reduced JVH in weaned piglets [41].…”
Section: Discussionsupporting
confidence: 78%
“…Conversely, levels of serum immunoglobulins (IgG, IgM, IgA) and IL-6 were increased in response to lower doses (8% or 10% FRM), while the inclusion of AN enhanced IgG but reduced the rests. A study showed that feeding of fermented products, such as the soybean meal, to weaned piglets significantly improved mucosal or systemic immunoglobulins [38,39,54,55]. The discrepancy between increased immunoglobulins and WBC counts could be related to the preferential activation of the adaptive immune responses, which culminate in the increment of immunoglobulins.…”
Section: Discussionmentioning
confidence: 99%
“…Fermented feeds based on protein sources (primarily soybean products) have, in previous studies, been reported to improve performance and gut health in weaned piglets [28][29][30] and poultry [8,17,31]. Certain brown macroalgae species have also been reported to have gut-health-promoting effects [32], but a low digestibility [33,34], which may limit their inclusion in diets for very young animals.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhu et al (2017), among the four different dietary treatments (each containing 0%, 5%, 10% and 15% FSBM, respectively), 10% FSBM diet was proved to be most effective in improving immunity and intestinal health in piglets. Roh et al (2015) also proved that 10% FSBM diet can modulate the expression of genes related to inflammatory responses in pigs.…”
Section: Introductionmentioning
confidence: 99%